Insights into innate and adaptive immune responses in vaccine development against EV-A71 - Lim, Hui Xuan *; Poh, Chit Laa * (Sage, 2019)
Enterovirus A71 (EV-A71) is one of the major causative agents of hand, foot and mouth disease (HFMD) in the world, infecting mostly infants and young children (<5 years of age) in Asia. Approximately 2 million cases of HFMD were reported in China each year, of which approximately 45–50% were due to EV-A71. Most of the HFMD infections caused by EV-A71 usually result in mild symptoms with rashes and ulcers in the mouth. However, virulent strains of EV-A71 can infect the central nervous system and cause severe neurologic diseases, leading to reduced cognitive ability, acute flaccid paralysis and death. The lack of understanding of cellular immunity for long-term protection from the HFMD disease represents a major obstacle for vaccine development. In particular, the role of innate and T cell immunity during HFMD infection remains unclear and there is evidence suggesting the importance of CD4+ and CD8+ T cells for protective immunity. Currently, no US FDA-approved vaccine is available for EV-A71. Although the inactivated vaccines produced in China are highly effective (vaccine efficacy >95%), they lack the cellular immunity required for long-term protection. In this review, we discuss the findings that support the protective roles of innate and T cell immunity against EV-A71 infection, which will provide the knowledge needed for the urgent development of efficacious vaccines that will confer long-term protection.